2017
DOI: 10.1002/gcc.22444
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of specific molecular profiles in pediatric acute megakaryoblastic leukemia in non‐Down syndrome

Abstract: Pediatric acute megakaryoblastic leukemia in non-Down syndrome (AMKL) is a unique subtype of acute myeloid leukemia (AML). Novel CBFA2T3-GLIS2 and NUP98-KDM5A fusions recurrently found in AMKL were recently reported as poor prognostic factors. However, their detailed clinical and molecular characteristics in patients treated with recent improved therapies remain uncertain. We analyzed molecular features of 44 AMKL patients treated on two recent Japanese AML protocols, the AML99 and AML-05 trials. We identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(100 citation statements)
references
References 36 publications
(81 reference statements)
3
95
0
2
Order By: Relevance
“…Indeed, genetic mutations involving GATA1 , KIT and FLT3 genes are less frequent in CBFA2T3‐GLIS2 ‐positive than in negative patients, being detected only in few cases. In the study reported by Hara et al (), genetic mutations were found in 14% of AMKL CBFA2T3‐GLIS2 ‐positive patients as compared to 35% of negative patients. The genes commonly involved are FLT3 , GATA1 and KIT (Hara et al , ) as well as RAS mutations and mutations in the JAK/STAT pathway (Table ) (Gruber et al , ; De Rooij et al , ).…”
Section: Mutation Pattern In Cbfa2t3‐glis2 Positive Leukaemiamentioning
confidence: 90%
See 2 more Smart Citations
“…Indeed, genetic mutations involving GATA1 , KIT and FLT3 genes are less frequent in CBFA2T3‐GLIS2 ‐positive than in negative patients, being detected only in few cases. In the study reported by Hara et al (), genetic mutations were found in 14% of AMKL CBFA2T3‐GLIS2 ‐positive patients as compared to 35% of negative patients. The genes commonly involved are FLT3 , GATA1 and KIT (Hara et al , ) as well as RAS mutations and mutations in the JAK/STAT pathway (Table ) (Gruber et al , ; De Rooij et al , ).…”
Section: Mutation Pattern In Cbfa2t3‐glis2 Positive Leukaemiamentioning
confidence: 90%
“…In the study reported by Hara et al (), genetic mutations were found in 14% of AMKL CBFA2T3‐GLIS2 ‐positive patients as compared to 35% of negative patients. The genes commonly involved are FLT3 , GATA1 and KIT (Hara et al , ) as well as RAS mutations and mutations in the JAK/STAT pathway (Table ) (Gruber et al , ; De Rooij et al , ). So far, an impact of the mutation burden on the outcome of CBFA2T3‐GLIS2 positive AML has not been demonstrated.…”
Section: Mutation Pattern In Cbfa2t3‐glis2 Positive Leukaemiamentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, haematopoietic stem cell transplantation (SCT) is generally not performed in infants with AML in the low‐ or intermediate‐risk group owing to its late side effects (Niewerth et al , ). However, CBFA2T3‐GLIS2 and NUP98‐KDM5A have been recently found to be poor prognostic markers (de Rooij et al , ; Hara et al , ). Thus, the establishment of a revised risk‐stratified therapy specific for infants with AML may improve treatment outcomes and reduce late side effects.…”
mentioning
confidence: 99%
“…Répartition des oncogènes de fusions les plus fréquents dans les LAM7 de novo. (selon [39] et [20]). B. Fréquences des mutations additionnelles observées dans les différents sous-groupes de LAM7 pédiatriques.…”
Section: Figure 1 Anomalies Génétiques Les Plus Récurrentes Des Lam7unclassified